2020
DOI: 10.3390/su122310201
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Management of Tourist Destinations: A New Approach to Strategic Management at the DMO Level by Integrating Lean Techniques

Abstract: Destination management organizations have a key role to play in the governance of tourism destinations, in managing destination networks and in ensuring good cooperation between stakeholders. Although, destination management organizations (DMOs) are atypical organizations, their operations are evaluated according to their organizational efficiency and effectiveness. This study aims to propose a framework to improve the management of the tourist destination through an innovative approach that interconnects stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 60 publications
0
33
0
3
Order By: Relevance
“…As known, DMOs are public or private organizations that work at different administrative levels to implement the tourism development and marketing policy of a destination [96]. In this case, Romanian DMOs organizations tend to have limited funding sources, budgets and tools to sustain a full range of tourism support services.…”
Section: Case Study: Romania As a Tourism Destinationmentioning
confidence: 99%
“…As known, DMOs are public or private organizations that work at different administrative levels to implement the tourism development and marketing policy of a destination [96]. In this case, Romanian DMOs organizations tend to have limited funding sources, budgets and tools to sustain a full range of tourism support services.…”
Section: Case Study: Romania As a Tourism Destinationmentioning
confidence: 99%
“…Gossling et al [47] observed that most economies around the world depend on Nigerian tourism sector as their backbone, which corroborates the fact that Nigerian tourism represents 9% of global trade for tourism in Africa [48]. Consequently, tourism is the fastest only significant and industry that improves the world economy and DMOs depend on tourists/visitors to support the economy [22,[49][50][51].…”
Section: Determinants Of Festival Satisfactionmentioning
confidence: 82%
“…The theory of planned behavior (TPB) has delivered sup-portive suggestions regarding social media marketing, festival quality, website quality, online word of mouth (eWOM), festival satisfaction, cultural motivation, and festival revisiting intention. This shows that the majority of research relating to digital technology focused solely on customer satisfaction in providing quality tourism services to tourists at many cultural destinations [22,50,52]. Therefore, value creation has been measured as a key to long-term success [53].…”
Section: Determinants Of Festival Satisfactionmentioning
confidence: 99%
“…In recent time, destination management have continued to dominate the discussion in the tourism management literature due to its significance to the sustainability of the hospitality industry and the development of the tourism sector, particularly in developing nations. Destination management encompasses the planning, organising and coordination of activities such as attractions, amenities, marketing, tours, accommodations and events targeted at enhancing tourist and visitors experience in the destination (Foris et al, 2020). It involves the development of policies, strategies and programmes that will create awareness on the unique story and attractiveness of the tourist destinations in order to attract tourist and visitors to the destination, and as well enhancing the revenue of the destination and the sustainability of the hospitality industry.…”
Section: Destinations Managementmentioning
confidence: 99%
“…Also, the services of tourism intermediaries such as tour agents, wholesalers, and online travel agencies contribute significantly to tourist and visitors experience. Management of tourism intermediaries is vital since their services involve informing potential tourist and marketing tourism products which could encourage tourist visit to the destination as well as increase the revenue of the destination and performance of the hospitality industry (Foris et al, 2020). Richards (2002) indicated that effective management of tourism intermediaries and attractions impact on the performance of destination and the hospitality industry.…”
Section: Management Of Tourism Intermediariesmentioning
confidence: 99%